RELATIONSHIP BETWEEN INTAKE CO AND HYPERTENSION INCIDENCE IN STREET VENDORS IN JAMBI CITY - Azzuhdi, Fadhel Alim; S, Oka Lesmana; Putra, Ashar Nuzulul; Sitanggang, Hendra Dhermawan; Rahmat, Andree Aulia (Jurnal Dunia Kesmas, 2025)
Hypertension is a non-communicable disease that has become a global health issue, including in Indonesia. Exposure to carbon monoxide (CO) in areas with heavy vehicle traffic is suspected to increase the risk of hypertension. This study analyzes the risk factors for hypertension among street vendors in high CO concentration areas, Simpang Tugu Juang Sipin, Jambi, in 2024. This research is an analytical quantitative study with a cross-sectional approach. Out of 53 samples, 48 respondents were analyzed using the total sampling technique. Data were collected through blood pressure measurements, smoking surveys, physical activity, and CO intake calculations using the ARKL method. Analysis was conducted univariately and bivariately using the chi-square test. The research findings indicate a significant relationship between CO intake (p=0.045) and smoking habits (p=0.022) with the incidence of hypertension among street vendors. Meanwhile, physical activity is included as a risk factor, but it does not show a statistically significant relationship (p>0.05). The conclusion of this study is that exposure to carbon monoxide (CO) and smoking habits are significantly associated with the incidence of hypertension, whereas physical activity, although classified as a risk factor, does not show a statistically significant relationship. Therefore, promotional and preventive interventions from health institutions are needed, as well as increased education and public awareness efforts to reduce the risk of hypertension.